Factors sustaining social enterprises from the tawhidic paradigm in Malaysia - Azan, Zaliza; Hamid, Zarinah; Mhd Sarif, Suhaimi; Ismail, Yusof (UUM Press, 2019)
This paper attempts to analyze the factors that sustain social entrepreneurship theory from Tawhidic paradigm perspective. It describes the nature of the social entrepreneurship, the scope and boundaries of assessment on social entrepreneurship environments, and the assessment of internal aspects social entrepreneurship entities in order to formulate, implement, and evaluate strategies for survival and growth. This paper also develops an alternative model as a means to achieve sustainability in terms of innovation and competitive advantage for social entrepreneurship. It uses in-depth interviews with 10 participants including policymaker, subject matter experts, and founders of social enterprises in Malaysia. The finding indicates that the Tawhidic approach contributes to the theoretical and practical understanding of the factors sustaining social enterprises in Malaysia. Future research should incorporate more participants to further debate the dynamics of key components in the subject matter of the study.